The 13th Conference of the International Sports Engineering Association 2020
DOI: 10.3390/proceedings2020049107
|View full text |Cite
|
Sign up to set email alerts
|

Are UCL Injuries a Matter of Bad Luck? The Role of Variability and Fatigue Quantified

Abstract: Upper extremity injuries are common in baseball. One of these is the ulnar collateral ligament (UCL) injury. In the field of sports injuries, most research focuses on average kinematics and kinetics between subjects, whereas focusing on within-subject variability appears to be more relevant for determining injury risk. We constructed a simple explanatory simulation model to illustrate the relationship between within-subject load variability and risk, illustrating how pitchers with a higher load variability are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The individual association of elbow load magnitude and within-individual variability with repetitive pitching emphasize the importance of an individual approach in relation to the quanti cation of load and overload. This individual approach seems essential in relation to overuse injuries because it is hypothesized that pitchers who have a higher load magnitude and within-individual variability are at higher risk for sustaining an injury 27 . This, in combination with the mechanical fatigue phenomenon, where an increase in loading cycles (pitch count) and loading magnitude (valgus torque) increases the chance of damage, are important factors in overuse injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The individual association of elbow load magnitude and within-individual variability with repetitive pitching emphasize the importance of an individual approach in relation to the quanti cation of load and overload. This individual approach seems essential in relation to overuse injuries because it is hypothesized that pitchers who have a higher load magnitude and within-individual variability are at higher risk for sustaining an injury 27 . This, in combination with the mechanical fatigue phenomenon, where an increase in loading cycles (pitch count) and loading magnitude (valgus torque) increases the chance of damage, are important factors in overuse injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The valgus torque magnitude on its own cannot completely explain this percentage, as all professional pitchers show high valgus torques. To explain this prevalence, the within-individual load variability and the injury threshold are both important metrics to include [13]. The injury threshold in this model is the maximal load the UCL can sustain before it strains or tears.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstrated within-individual valgus torque variability and the fact that this differs between subjects is a step towards validating the injury model of van Trigt et al (2020). However, it is suggested that pitchers who throw with a higher magnitude and within-individual variability of valgus torque might have-but do not necessarily have-a higher chance of sustaining an injury, because the injury threshold is also of importance [13] (Figure 2). It is important to mention that we did not investigate the relationship between valgus torque variability and injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations